2017
DOI: 10.1186/s12871-017-0324-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine combined with sufentanil for post- thoracotomy intravenous analgesia:a randomized, controlled clinical study

Abstract: BackgroundFew studies have investigated the use of dexmedetomidine in patient-controlled intravenous analgesia (PCIA) after thoracic surgery. This study to evaluate the effect of dexmedetomidine combined with sufentanil for PCIA after thoracotomy under general anaesthesia.MethodsNinety-seven adults patients scheduled for thoracotomy surgery. All two groups received PCIA with either sufentanil alone (control group) or combining dexmedetomidine with sufentanil (dexmedetomidine group). Hemodynamic measurements, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
4
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 32 publications
3
48
4
2
Order By: Relevance
“…PONV are common complications for patients who received opioids. Many researches have agreed that DEX could reduce the incidence and severity of PONV in different surgery . Although our meta‐analysis found that the incidence of PONV was decreased in group DEX in our study, there was no significant difference between the anaesthetic‐with‐DEX and the without‐DEX groups.…”
Section: Discussioncontrasting
confidence: 73%
“…PONV are common complications for patients who received opioids. Many researches have agreed that DEX could reduce the incidence and severity of PONV in different surgery . Although our meta‐analysis found that the incidence of PONV was decreased in group DEX in our study, there was no significant difference between the anaesthetic‐with‐DEX and the without‐DEX groups.…”
Section: Discussioncontrasting
confidence: 73%
“…In PCIA group, the median number of pain score on coughing was 5 in the first day of post-operation ( Table 5) which suggested that about half patients may not receive adequate analgesia in the early postoperative period. Since the dose of sufentanil in this group is 0.05µg•kg-1•h-1, which was considered high in most clinical practices [22,23], increasing the dose of sufentanil may raise risk of side effects.…”
Section: Resultsmentioning
confidence: 99%
“…It was well demonstrated that hydromorphone has valuable advantages of rapid onset, robust analgesic efficacy, no ceiling effect for analgesia, inactive metabolite, and fewer side effects while compared to morphine [ 8 10 ]. Sufentanil, a highly selective mu opioid agonist, provides various advantages such as reliable analgesic efficacy, stable hemodynamics, and few side effects, and has been widely used as an postoperative analgesia in China [ 11 , 12 ]. Rapp et al reported that hydromorphone improved the mood of patients while compared to morphine [ 13 ].…”
Section: Introductionmentioning
confidence: 99%